2019
DOI: 10.1002/med.21592
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism(s) of action of antioxidants: From scavenging reactive oxygen/nitrogen species to redox signaling and the generation of bioactive secondary metabolites

Abstract: Small molecule, dietary antioxidants exert a remarkably broad range of bioactivities, and many of these can be explained by the influence of antioxidants on the redox homeostasis. Such compounds help to modulate the levels of harmful reactive oxygen/nitrogen species, and therefore participate in the regulation of various redox signaling pathways. However, upon ingestion, antioxidants usually undergo extensive metabolism that can generate a wide range of bioactive metabolites. This makes it difficult, but other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 202 publications
(385 reference statements)
0
86
0
4
Order By: Relevance
“…In fact, abnormal protein S-glutathionylation is related to diverse cellular detrimental changes, including protein aggregation, protein degradation, apoptosis and mitochondrial dysfunction [215]. A thiol redox system consisting of the glutathione system (glutathione/glutathione reductase/glutaredoxin/glutathione peroxidase) and the thioredoxin system (thioredoxin/thioredoxin peroxidase (peroxiredoxins)/sulfiredoxin/thioredoxin reductase [216] are believed to be the major players in redox status regulation [99,[217][218][219]. Further, the thioredoxin system is an important thiol/disulphide redox controller ensuring the redox homeostasis [220].…”
Section: Nad(p)h Quinone Oxidoreductase-1 Nqo1mentioning
confidence: 99%
“…In fact, abnormal protein S-glutathionylation is related to diverse cellular detrimental changes, including protein aggregation, protein degradation, apoptosis and mitochondrial dysfunction [215]. A thiol redox system consisting of the glutathione system (glutathione/glutathione reductase/glutaredoxin/glutathione peroxidase) and the thioredoxin system (thioredoxin/thioredoxin peroxidase (peroxiredoxins)/sulfiredoxin/thioredoxin reductase [216] are believed to be the major players in redox status regulation [99,[217][218][219]. Further, the thioredoxin system is an important thiol/disulphide redox controller ensuring the redox homeostasis [220].…”
Section: Nad(p)h Quinone Oxidoreductase-1 Nqo1mentioning
confidence: 99%
“…While nitric oxide is an essential chemical mediator of physiological processes in vivo, it can also generate free radicals in aerobic conditions. Plant products are found to scavenge nitrogen derived free radicals as well (Hunyadi 2019 ). 10 µg/ml of P.guajava leaf extract displayed a nitric oxide scavenging activity of 53.1% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent review, we suggested that it may be a relevant, yet unexplored drug discovery strategy to perform systematic studies on chemically oxidized mixtures obtained from the biomimetic oxidation of small molecule antioxidants [ 5 ]. This is based on the notion that i) scavenging reactive oxygen or nitrogen species (ROS or RNS, respectively, collectively referred to as RONS) with antioxidants frequently results in chemically stable, bioactive, oxidized metabolites, ii) such metabolites may have a dramatically altered bioactivity compared to their parent compound, and iii) this altered bioactivity is due to new chemical information directly translated from oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the notion that i) scavenging reactive oxygen or nitrogen species (ROS or RNS, respectively, collectively referred to as RONS) with antioxidants frequently results in chemically stable, bioactive, oxidized metabolites, ii) such metabolites may have a dramatically altered bioactivity compared to their parent compound, and iii) this altered bioactivity is due to new chemical information directly translated from oxidative stress. Therefore, this chemical metabolite space, that we defined as the scavengome, should be particularly rich in bioactive compounds [ 5 ].…”
Section: Introductionmentioning
confidence: 99%